The Role of the Lateral Soft Tissues in Controlling Anterior Translation And Internal Rotation of the Tibia, and An Investigation of Lateral Reconstructions Accompanying ACL Reconstruction - Williams,A; Stephen,J; Kittl,C; Inderhaug,E; El-Daou,H; Dodds,A; Halewood,C; Amis,A (Orthopaedic journal of sports medicine, 2017)
Introduction: There is considerable current interest in the role of the lateral soft tissue structures in the context of ACL deficiency (ACLD). Of course the topic is not new but a re-visitation, although with improved experimental techniques available. It was clear that there was a rush to create surgical techniques based on the ‘Anterolateral Ligament’ (ALL) but without investigative ‘due-diligence’ and without consideration that other structures may be important, or more important. Objectives: To study the anatomy and biomechanics of the lateral soft tissues relevant to the ACL and ACL reconstruction techniques investigating isometricity, structures’ contributions to resistance of anterior tibial translation (ATT), internal rotation (IR), and pivot shift (PS). Also we studied the impact of various reconstructions on restoration of kinematics and potential over-constraint and effects on articular surface compression load. Methods: Several studies were undertaken. In all healthy fresh-frozen cadaveric specimens were used. Descriptive anatomy was described. Length changes of suture fixed at structure and reconstruction attachment points on the tibia and femur were measured with linear variable displacement transducers (LVDTs). To investigate structures’ contribution to resist translation and torque a 6-degrees of freedom robot with a universal force-moment sensor was used in a classic ‘cutting study’. The robot replayed the same movement with sequential sectioning of structures recording the decrease in force / torque needed to reach the same movement limit. In this way the structure’s resistance to motion as a percentage of the total could be calculated. In other studies knees were mounted in a test rig where knee kinematics were recorded from 0° to 100° of flexion by use of an optical tracking system. Joint surface compression was measured w